Study on effects of surface albedo on outdoor environment using actual scale models - Lim, Zheng Wei (2019)
More people are staying in cities as the world moves quickly towards urbanisation today, staying at high-rising buildings. Building these infrastructures mean forests have to pave the way for them. A reduction in vegetation, coupled with tall buildings also leads to a fall in wind ventilation. These surfaces absorb the heat in the day and release them at night, causing the region to be warmer. People combat this problem by using the air-conditioner. Due to the inefficiencies of the machine, the majority of the waste energy is converted as heat. This further compounds the existing problem, giving rise to Urban Heat Island (UHI) effect. This report presents an experimental study on the effects of albedo on the outdoor environment using actual scale models at Tuas. To evaluate the effectiveness of the paint, the surface temperature, heat flux activities and indoor temperature of the set up was studied. Two buildings were used as the control setup, and cool painting was used on the other two units as a test site to evaluate the effects of cool paint on the buildings and the surroundings. The building façade coated with the cool paint was found to have a lower surface temperature as compared to the façade with conventional paint. Both the outer and inner walls of the building experienced a reduction in surface temperature of about 2°C. The application of cool paint on the pavement managed to result in an approximately 13°C maximum surface temperature reduction. The application of cool paint to the roof, much like the façade, reduced both the outer and inner surfaces by approximately 3°C. From the experiments, it can be seen that usage of cool paint can effectively reduce the thermal loading in buildings, and at the same time improve thermal comfortability within the canyon.